(本小题满分14分)
(Ⅰ)设等比数列{a n}的公比为q,∵a n>0,∴q>0
若q=1时S m=ma 1S 2m=2ma 1,此时2S m=S 2m,而已知S m=26,S 2m=728,∴2S m≠S 2m,∴q=1不成立…(1分)
若q≠1,由
S m =26
S m =728 得
a 1 (1- q m )
1-q =26(1)
a 1 (1- q 2m )
1-q =728(2) …(2分)
(1)÷(2)得:1+q m=28∴q m=27…(3分)
∵q m=27>1∴q>1
∴前m项中a m最大∴a m=18…(4分)
由 a 1 q m-1 =18 得,
a 1 q m-1
q m =
18
27 ∴
a 1
q =
2
3 (3) 即 a 1 =
2
3 q
把 a 1 =
2
3 q 及q m=27代入(1)式得
2
3 q(1-27)
1-q =26
解得q=3
把q=3代入 a 1 =
2
3 q 得a 1=2,所以 a n =2× 3 n-1 …(7分)
由 T n =2 n 2
(1)当n=1时 b 1=T 1=2
(2)当 n≥2时 b n = T n - T n-1 =2 n 2 -2(n-1 ) 2 =2 n 2 -2( n 2 -2n+1) =4n-2
∵b 1=2适合上式∴b n=4n-2…(9分)
(Ⅱ)由(1)得 c n =(4n-2)•2× 3 n-1 =4(2n-1)× 3 n-1
记 d n =(2n-1)× 3 n-1 ,d n的前n项和为Q n,显然P n=4Q nQ n = d 1 + d 2 + d 3 +…+ d n =1× 3 0 +3× 3 1 +5× 3 2 +…+(2n-1)× 3 n-1 …①∴ 3 Q n = d 1 + d 2 + d 3 +…+ d n =1× 3 1 +3× 3 2 +5× 3 3 +…+(2n-1)× 3 n …..②
…(11分)
①-②得:-2Q n=1+2×3 1+2×3 2+2×3 3+…2×3 n-1-(2n-1)×3 n
= 1+2×
3(1- 3 n-1 )
1-3 -(2n-1)× 3 n =-2-(2n-2)×3 n…(13分)
∴ 4 Q n =4(n-1)× 3 n +4 ,
即 P n =4(n-1)× 3 n +4 …(14分)